Assessment of Urinary Tract Infection and Cytokine (IL-2, IL-4 and IL-17A) Serum Levels in Iraqi Samples of Systemic Autoimmune Diseases (Rheumatoid Arthritis, Ankylosing Spondylitis and Systemic Lupus Erythematosus) Patients - Ad’hiah, Professor Dr. Ali H. (IIUM Medical Journal Malaysia, 2013)
Introduction: Aetiopathogenetic mechanisms that lead to autoimmune diseases are complex, but Urinary tract infection (UTI) and cytokines have been suggested to mediate important effects. Methods: UTI and serum levels of three cytokines (IL-2, IL-4 and IL-17A) were assessed in 98 rheumatoid arthritis (RA), 33 ankylosing spondylitis (AS) and 20 systemic lupus erythematosus (SLE) Iraqi patients, as well as 45 controls. Results: Out of 151 systemic autoimmunity patients, 23.8% were observed to have UTI, and such frequency was approximated in RA, AS and SLE (23.5, 27.3 and 20.0%, respectively), while in controls, it was 11.1%. Two pathogens were identified as a cause of UTI; E. coli and Proteus spp. In total patients, E. coli was present as a single causative pathogen in 10.6%, while for Proteus spp. it was 8.6%, in addition to 4.6% of mixed infection. The corresponding frequencies were 10.2, 8.2 and 5.1% in RA, 15.2, 6.1 and 6.1% in AS, 5.0, 15.0 and 0.0 in SLE and 8.9, 0.0 and 2.2% in controls, respectively. IL-2 was significantly increased in total patients (21.68 vs. 9.66 pg/ml), as well as RA, AS and SLE (25.10, 24.06 and 14.16 pg/ml, respectively) compared to controls. A similar increase was observed in UTI+ve versus UTI-ve cases in total patients, AS and SLE, but not RA or controls. Such differences were less clear in IL-4, while IL-17A showed no significant variations. Conclusion: UTI represents an important clinical complication in systemic autoimmunity and IL-2 also has its role in the pathogenesis.